A novel measuring module for spindle rotational accuracy based on virtual instrument. (November 2017) - Chen, Ye; Zhao, Xiangsong; Gao, Weiguo; Hu, Gaofeng; Zhang, Shizhen; Tian, Yanling
The spindle rotational accuracy is an important indicator to evaluate the characteristic of a machine tool. In this article, an easy-to-use measuring module is proposed based on virtual instrument platform. A new method for measuring rotational speed and angular orientation using an adaptive filtering method to processing the target installation eccentricity is proposed, instead of using the encoder. This method can reduce the measuring cost and make the measurement more convenient, without affecting the measuring accuracy. Meanwhile, the selective principle of target installation eccentricity for rotating sensitive direction is investigated by theoretical analysis and numerical simulation. Based on the proposed method, measuring module is developed. National Instruments data acquisition card and capacitive sensors are used to acquire the displacement signals of the spindle rotational error motion. Contrast experiments with the commercial measuring software are performed to validate the feasibility and repeatability of the proposed measuring module. The experimental results demonstrate that the developed measuring module can reach the same precision using less test parameters.